2017
DOI: 10.1093/mnrasl/slx115
|View full text |Cite
|
Sign up to set email alerts
|

Radio mode feedback: Does relativity matter?

Abstract: Radio mode feedback, associated with the propagation of powerful outflows in active galaxies, is a crucial ingredient in galaxy evolution. Extragalactic jets are well collimated and relativistic, both in terms of thermodynamics and kinematics. They generate strong shocks in the ambient medium, associated with observed hotspots, and carve cavities that are filled with the shocked jet flow. In this Letter, we compare the pressure evolution in the hotspot and the cavity generated by relativistic and classical jet… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 37 publications
3
26
1
Order By: Relevance
“…Then, time averagely, the pressure of the jet coincides with that of the cocoon due to the confinement of the jet by the cocoon. The internal energy and mass of the cocoon garnered through the reverse shock during the jet injection time, t, thus are estimated, when all the physical quantities characterizing the jet, such as jet radius, density, pressure, velocity, and Lorentz factor, are treated as the "temporally averaged" values, as follows: (Martí et al 1997;Bromberg et al 2011;Perucho et al 2017), where subscripts j and c stand for the jet and cocoon respectively. Here, V c is the volume of the cocoon, r j is the jet radius, h := 1 + ΓP/(Γ − 1)ρc 2 is the dimensionless specific enthalpy and v h is the propagation velocity of the jet head.…”
Section: Analytic Prediction On Stability Of Relativistic Jet Interfacementioning
confidence: 99%
“…Then, time averagely, the pressure of the jet coincides with that of the cocoon due to the confinement of the jet by the cocoon. The internal energy and mass of the cocoon garnered through the reverse shock during the jet injection time, t, thus are estimated, when all the physical quantities characterizing the jet, such as jet radius, density, pressure, velocity, and Lorentz factor, are treated as the "temporally averaged" values, as follows: (Martí et al 1997;Bromberg et al 2011;Perucho et al 2017), where subscripts j and c stand for the jet and cocoon respectively. Here, V c is the volume of the cocoon, r j is the jet radius, h := 1 + ΓP/(Γ − 1)ρc 2 is the dimensionless specific enthalpy and v h is the propagation velocity of the jet head.…”
Section: Analytic Prediction On Stability Of Relativistic Jet Interfacementioning
confidence: 99%
“…Subsequent hydrodynamical (HD) simulations started inflating bubbles self-consistently via a subgrid jet model (Sternberg & Soker 2008). On these scales, the jet is assumed to be sufficiently slow such that nonrelativistic HD can be used (but see Perucho et al 2017). A propagating jet introduces significant heating through the dissipation of the accompanying bow shock (e.g., Reynolds et al 2002;.…”
Section: Introductionmentioning
confidence: 99%
“…Actually, a large portion of the injected energy through the jet channel is transferred to the ambient medium. In reference [20], the authors showed that this is directly related to the relativistic nature of AGN jets. The concentration of high energy and momentum fluxes through a narrow channel favours high post-shock pressure:…”
Section: Frii Jetsmentioning
confidence: 99%